Fast solution of large N× N matrix equations in an MIMD–SIMD Hybrid System - Chin Sim, Leo; Leedham, Graham; Chin Jian, Leo; Schroder, Heiko (Parallel computing, 2003)
In this paper, we propose a new high-speed computation algorithm for solving a large N× N matrix system using the MIMD–SIMD Hybrid System. The MIMD–SIMD Hybrid System (also denoted as Hybrid System in this paper) is a new parallel architecture consisting of a combination of Cluster of Workstations (COWs) and SIMD systems working concurrently to produce an optimal parallel computation. We first introduce our prototype SIMD system and our Hybrid System setup before presenting how it can be implemented to find the unknowns in a large N× N linear matrix equation system using the Gauss–LU algorithm. This algorithm basically performs the ‘Divide and Conquer’ approach by breaking down the large N× N matrix system into a manageable 32 × 32 matrix for fast computation.